Design of Wireless Acceleration Sensor Nodes Used in Mechanical Equipment Status Monitoring - G. Vamshi Kishore; J. Suresh (Institute of Advanced Engineering and Science, 2017)
Wireless Sensor Network is a new integrated technology, which combines sensor technology, wireless communication technology, Micro-Electro-Mechanical Systems technology and Digital electronic technology. Now, it has been widely used in military, industrial control, environmental monitoring, transportation, and medical. Along with the research evolution on Wireless Sensor Network, its application fields are gradually expanding. It is penetrating deep into each aspect of the human’s production and life, and will be a new revolutionary technology. In this paper, a wireless acceleration node based on wireless single chip processor CC2430, an ARM7TDMI-S core based microcontroller called LPC2478 microprocessor and three-axis acceleration sensor ADXL330 is designed to monitor the mechanical system operation conditions and fault diagnosis with high efficiency. The performance and characteristics of CC2430, ADXL330 and LPC2478 are introduced compactly. The designations of hardware as well as software of wireless network node are introduced in details. The nodes perform steadily and efficiently in practical test, and it can be easily applied to other monitoring areas.